KEBERADAAN KAPANG PADA GAPLEK: PENGARUH TERHADAP KUALITAS DAN DAYA SIMPAN - Titin Yulineri; Riani Hardiningsih; Suciatmih Suciatmih (Research Center for Biology-Indonesian Institute of Sciences, 1997)
A study was carried out to find out contaminated fungi on dried cassava.There were two experiments: I. isolation and identification of fungi on dried cassava and 2. inhibiting capacity of some kinds of some kinds of solution on growth of fungi.In experiment 2, there were three treatments: I.solution of garlic; 2.solution of salt and 3. vinegar.Results showed that dominated fungi on dried cassava were Aspergillus niger. Pen/ol/iumsp.and Rhizopussp. Between three treatments in experiment 2, the most effective solution to increase quality and storage capacity of dried cassava was solution of garlic.